Effect of ibuprofen and low-intensity pulsed ultrasound on the reduction of pain after initial archwire placement: a double-blind randomized clinical trial - Fahimeh Farzanegan; Zahra Ahmadi Bamrood; Abdolrasoul Rangrazi; Hooman Shafaee (Universidad de Concepción., 2022)
Objective: This study aimed to compare the effect of ibuprofen and low-intensity pulsed ultrasound (LIPUS) on the reduction of pain after the placement of initial archwire in orthodontic patients. Material and Methods: This double-blind clinical trial study was carried out on 60 female candidates for fixed orthodontic treatment referring to the Orthodontic Department of School of Dentistry in Mashhad University of Medical Sciences, Mashhad, Iran, during 2015-2016. The subjects were divided into four groups of ibuprofen, LIPUS, placebo, and mock LIPUS. A questionnaire and a rectangular and flexible cubic silicone were given to each patient to record the severity of pain based on the visual analog scale at specified time points (i.e., 2 h, 6 h, at bedtime, 2nd, 3rd, and 7th days after archwire placement) when biting the silicone block with the anterior and posterior teeth and without biting at all. Repeated measures analysis of variance was used in order to compare the pain severity at different time points. Results: The comparison of pain severity at various time points showed that the highest and lowest mean scores of pain were reported at bedtime and seven days after the intervention (p<0.001). In each of the three conditions (i.e., biting the silicone block with the anterior and posterior teeth and without biting the teeth) at six time points (i.e., 2 h, 6 h, at bedtime, 2nd, 3rd, and 7th days following archwire placement), no significant difference was observed in the severity of pain (p>0.05). Conclusion: In conclusion, LIPUS (with a frequency of 1 MHz and an intensity of 100 mW) and ibuprofen have no significant effects on reduction of the pain severity at different time points and various conditions in orthodontic patients.